"It's like she's talking about me" — Exploring the value and potential impact of a YouTube film presenting a qualitative evidence synthesis about chronic pain: An analysis of online comments. Issue 3 (1st September 2020) - Toye, Francine; Seers, Kate; Barker, Karen
ABSTRACT: Background: There is very limited research exploring the value and impact of qualitative research in chronic pain despite the large volume of research. Aims: The aim of this study was to find out whether viewers' comments in response to a YouTube film, portraying findings from a qualitative evidence synthesis about living with pain, revealed any potential value or impact to viewers. Methods: We collected online data posted in response to the film Struggling to Be Me . We used themes from a large review of qualitative research as an a priori analytic framework. We used inductive thematic analysis to distil the essence of data that did not fit this framework. A thematic analysis of online comments to evaluate the impact of an arts-based health research film on people living with chronic pain is presented. Results: We developed two inductive themes that explored the value and potential impact of watching the film online: (1) It has given voice to our suffering and (2) it makes me feel that I am not alone. Two subthemes added insight to the a priori framework: First, I have had enough of me added insight to the theme my life is impoverished and confined ; second, I am treated like a criminal because I take opioids added insight to the theme lost personal credibility . Conclusions: Our findings indicate that watching the YouTube film has potential value and impact, giving voice to suffering and making people feel that they are not alone. There are specific ethical challenges relating to internet-mediated research.